Measurement invariance of the Driver Behavior Questionnaire across samples of young drivers from Finland and Ireland. (May 2015) - Mattsson, Markus; Fearghal, O'Brien; Lajunen, Timo; Gormley, Michael; Summala, Heikki
Highlights: Different DBQ factor structures are compared across two countries. Measurement invariance is investigated. Partial strong invariance holds for only one factor, slips. Partial weak invariance holds for one factor, lapses. Self-reported violations are different in nature in the two countries. Abstract: This article investigates the factor structure of the 27-item Driver Behavior Questionnaire (DBQ) in two samples of young drivers (18–25 years of age); one from Finland and the other from Ireland. We compare the two-, three-, and four-factor solutions using Confirmatory Factor Analysis (CFA) and show that the four-factor model (with the latent variables rule violations, aggressive violations, slips and lapses) fits the data from the two countries best. Next, we compare the fit of this model across samples by the means of a measurement invariance analysis in the CFA framework. The analysis shows that the four-factor model fails to fit both samples equally well. This is mainly because the socially-oriented latent variables (rule violations and aggressive violations) are different in nature in the two samples. The cognitively-oriented latent variables (slips and lapses) are, however, similar across countries and the mean values of slips can be compared using latent variable models. However, the common practice of calculating sum scores to represent the four latent DBQ variables and comparing them across subgroups of respondents is unfounded, at least when comparing young respondents from Finland and Ireland.